2001
DOI: 10.1007/bf02345294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of time-frequency distribution techniques for analysis of spinal somatosensory evoked potential

Abstract: Spinal somatosensory evoked potential (SSEP) has been employed to monitor the integrity of the spinal cord during surgery. To detect both temporal and spectral changes in SSEP waveforms, an investigation of the application of time-frequency analysis (TFA) techniques was conducted. SSEP signals from 30 scoliosis patients were analysed using different techniques; short time Fourier transform (STFT), Wigner-Ville distribution (WVD), Choi-Williams distribution (CWD), cone-shaped distribution (CSD) and adaptive spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The first type of abnormality gives rise to the dissociation of excitation, which lengthens the latency and lowers the amplitude of the wave. Relative characteristic changes in magnitude and latency (Kang et al, 2009; Madhok et al, 2010), conduction velocity (Salami et al, 2003) and time-frequency distributions (Hu et al, 2001; Hu et al, 2002), have all been studied in the past decades and are commonly used as SSEP measurement parameters in both laboratory experiments and clinical situations (De Giorgio et al, 1993; Robinson et al, 2003; Rossetti et al, 2010; Rothstein, 2000; Young et al, 2004). The other type of abnormality is the altered or disturbed connection induced by the alterations to the neural signals and sources that occur after ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…The first type of abnormality gives rise to the dissociation of excitation, which lengthens the latency and lowers the amplitude of the wave. Relative characteristic changes in magnitude and latency (Kang et al, 2009; Madhok et al, 2010), conduction velocity (Salami et al, 2003) and time-frequency distributions (Hu et al, 2001; Hu et al, 2002), have all been studied in the past decades and are commonly used as SSEP measurement parameters in both laboratory experiments and clinical situations (De Giorgio et al, 1993; Robinson et al, 2003; Rossetti et al, 2010; Rothstein, 2000; Young et al, 2004). The other type of abnormality is the altered or disturbed connection induced by the alterations to the neural signals and sources that occur after ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…2), which has been previously reported in several studies (Hu et al 2001a(Hu et al , 2002(Hu et al , 2003, while noise in other region (RONI) in the time- 5 The assessment of the minimum number of trials to detection SEP responses. All the indicative SEP parameters (CC, P37 amplitude, N45 amplitude, P37-N45 amplitude, and phase values), which were sensitive to the stimulus intensity, were used to assess the minimum number of trials that can significantly distinguish the resting EEG and SEP responses.…”
Section: Multiple Linear Regression In the Time-frequency Domainmentioning
confidence: 97%
“…The explored frequencies were ranged from 21 to 200 Hz in steps of 1 Hz in this study. Previous studies have shown that most meaningful time-frequency features of SEPs are distributed in the specified frequency range (Hu et al 2001a(Hu et al , 2002(Hu et al , 2003Zhang et al 2009). The squared magnitude of F(s, f) is called the scalogram.…”
Section: Time-frequency Domain Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…To provide timevarying spectral information on SEP waveforms, various time-frequency analysis (TFA) methods have been adopted and compared [3][4][5][6][7]. The short time Fourier transform (STFT) was recommended in [5][6][7] as an appropriate method for TFA of SEP signals and it was capable of revealing stable and easily identifiable characteristics -the parameters associated with the main peak in the time-frequency distribution (TFD) obtained by STFT.…”
Section: Introductionmentioning
confidence: 99%